2021
DOI: 10.5935/1984-0063.20200090
|View full text |Cite
|
Sign up to set email alerts
|

National Survey on the importance of sleep in the quality of academic life and mental health of college students in Portugal

Abstract: The academic years are a period of vulnerability when considering sleep problems and mental health. Growing evidence suggests poor sleep patterns are related to impaired academic life and lower psychological well-being. The aim of this study was to explore the importance of sleep habits and report the associations of sleep problems with quality of academic life and different dimensions of mental health (e.g. worries, anxiety, self-regulation and resilience) in a large sample of college students. The HBSC/JUnP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Poor sleep quality was common, with more than half of the students reporting abnormal, albeit mild, sleep disruption. Although direct comparisons are not necessarily easy, as published studies on poor sleep in university students are heterogeneous for country, student populations, questionnaire/assessment tools, and/or questionnaire thresholds utilized, our results seem slightly more encouraging than those of Reis et al (2021) , who recently reported a prevalence of insomnia of 67.7% in college students in Portugal, and those of Driller et al (2021) , who reported 67% between bad and moderate sleepers among first-year health degree undergraduates in New Zealand. Despite reasonable sleep duration, social jetlag ( Wittmann et al, 2006 ; Korman et al, 2020 ) was also common.…”
Section: Discussionmentioning
confidence: 54%
“…Poor sleep quality was common, with more than half of the students reporting abnormal, albeit mild, sleep disruption. Although direct comparisons are not necessarily easy, as published studies on poor sleep in university students are heterogeneous for country, student populations, questionnaire/assessment tools, and/or questionnaire thresholds utilized, our results seem slightly more encouraging than those of Reis et al (2021) , who recently reported a prevalence of insomnia of 67.7% in college students in Portugal, and those of Driller et al (2021) , who reported 67% between bad and moderate sleepers among first-year health degree undergraduates in New Zealand. Despite reasonable sleep duration, social jetlag ( Wittmann et al, 2006 ; Korman et al, 2020 ) was also common.…”
Section: Discussionmentioning
confidence: 54%
“…Impaired sleep was reported by 42% of our respondents, lower than the US (62%), Portugal (68%), and Ethiopia (56%) [ 31 , 32 , 99 ]. We found that more females experienced high sleep latencies, sleep disturbances, and daytime dysfunctions, supporting similar sex differences in Ethiopia [ 32 ].…”
Section: Discussionmentioning
confidence: 87%
“…Given the above findings, multipronged strategies need an overarching focus highlighting the health–academic achievement links, e.g., insomnia, excessive alcohol and dehydration that are associated with poorer academic performance and cognition [ 96 , 99 , 121 , 122 , 123 ]. Efforts should consider student participation in all student health promotion processes, target the student body, and particularly the identified risk groups e.g., males (lower FVC), females (eating more during stress), and BSc students (poorer nutrition/sleep quality, more ATOD use).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that research shows that almost half of students who report good sleep quality are classified as having poor sleep quality according to validated measurement instruments 22. The reduced percentage of students without sleeping problems53 may affect academic success in higher education since sleeping problems are associated with poorer academic performance,18 54 and women are more severely affected than men 55. Balancing time commitments between academic studies and social life can be difficult for students in higher education and may contribute to the lack of adequate sleep duration, especially for first-year students who are adjusting to the university environment 21.…”
Section: Discussionmentioning
confidence: 99%
“…Sleeping well is essential for health, well-being, quality of life and cognitive and physical performance 17. Sleeping well has been associated with less anxiety, more resilience18 and better academic performance 19. Sleep allows the body and brain to recover17 and may contribute to balance in life for students during higher education 20.…”
Section: Introductionmentioning
confidence: 99%